Analyzing the Internal Environment to Build Competitive Advantage: A Systematic Literature Review - Wijaksana, Dian Dwi; Zahro, Dinda Ratu; Saputri, Yuliana; Gayatri, Karinda; Grace s, Fill Ina; Simbolon, Friska; Kuswanto, Kuswanto; Sholeh, Ahmad; Wahyuni, Sri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The rapid development of digital technology, globalization, and the increasing intensity of business competition in recent years have made internal environment analysis an increasingly crucial aspect in determining an organization’s competitive advantage. This article aims to comprehensively synthesize the concepts and applications of internal environment analysis, including resources and capabilities, value chain analysis, core competencies, and SWOT analysis in the context of modern business. The method used is a Systematic Literature Review (SLR) by examining 30 scientific articles obtained from Google Scholar, SINTA, and accredited journals within the 2021–2026 period. The selection process was carried out through stages of screening titles, abstracts, and full texts based on predetermined inclusion criteria. The synthesis results indicate a shift from partial internal analysis approaches toward more integrative approaches, where organizational success is determined by the ability to manage resources, optimize the value chain, and develop core competencies that are adaptive to external environmental changes. In addition, SWOT analysis remains a dominant tool; however, it tends to be static and requires data-driven development. This article concludes that the integration of traditional approaches with the utilization of digital technology is key to enhancing the effectiveness of internal environment analysis in the modern business era.